Aprendizaje basado en problemas para mejorar la competencia indaga mediante métodos científicos para construir conocimientos en estudiantes de quinto grado de secundaria en el Colegio Parroquial Sagrada Familia de Belén 2022 - Melendez Ramirez, Ernesto Edin (2023)
This study's goal was to assess how problem-based learning improved fifth-grade high school students' capacity for scientific inquiry from the Sagrada Familia de Belén Parish School 2022 in the competence of inquiring through scientific methods to build knowledge, where used a contemporary, univariate, data collection methods included univariate and quasi-experimental transectional field designs with control groups, pre- and post-tests, a sample size of 55 students, and a valid and reliable performance test. The post-test findings revealed that the experimental group outperformed the control group in terms of average on the vigesimal scale (11,873>9,383) and in each of the dimensions: Problematize situations (10,455>8,283), design strategies (10,873>10,288), generates and records data or information (12,063>9,712), analyzes data and information (11,531 > 8,466), evaluates and communicates (12.5 > 9,185). Therefore, it is concluded that Problem-Based Learning does notably improve research competence in the students of the study population, since the p-value was 0.002, being lower than the established significance level, which is α = 0. .05